Nanoparticle Decorated Ultrathin Porous Nanosheets as Hierarchical Co(3)O(4) Nanostructures for Lithium Ion Battery Anode Materials - Mujtaba, Jawayria (Sci Rep, 2016)
We report a facile synthesis of a novel cobalt oxide (Co(3)O(4)) hierarchical nanostructure, in which crystalline core-amorphous shell Co(3)O(4) nanoparticles with a bimodal size distribution are uniformly dispersed on ultrathin Co(3)O(4) nanosheets. When tested as anode materials for lithium ion batteries, the as-prepared Co(3)O(4) hierarchical electrodes delivered high lithium storage properties comparing to the other Co(3)O(4) nanostructures, including a high reversible capacity of 1053.1 mAhg(−1) after 50 cycles at a current density of 0.2 C (1 C = 890 mAg(−1)), good cycling stability and rate capability.